Kurdish Issue and its Reflections in the Newspaper Ma'arif Israelis In (1961-1968) - Rahman , Qaraman Haydar; Hasan, Arazu Yousf (Zanco Journal of Human Sciences, 2024)
This research on the Kurdish issue in the newspaper Ma'arif during the years (1961-1968) emphasizes the attitude and attention to the Kurdish issue in the newspaper Ma'arif, by highlighting the inner side of events within the news and data of the newspaper The research consists of an introduction and three topics. The first topic is a summary of the newspaper's, the method of publication and the editorial board. The second topic is the Kurdish issue in two periods The newspaper's position during the negotiations and the rapprochement between the Kurds and the government is presented, referring to the external position on this issue